Influence of Hospital Volume Effects and Minimum Caseload Requirements on Quality of Care in Pancreatic Surgery in Germany - Krautz, Christian; Denz, Axel; Grützmann, Robert; Weber, Georg (Visceral Medicine, 2017)
Numerous international studies have identified hospital volume as significant independent variable of death following pancreatic surgery. Most of these studies were limited to regions of countries or portions of a national population and did not include data on volume-outcome effects in Germany.The Medline database was systematically searched to identify studies that analyzed volume-outcome relationships and effects of minimum caseload requirements on outcomes of pancreatic surgery in Germany.Recent observational studies utilizing German hospital discharge data confirmed that patients undergoing pancreatic surgery in Germany also have better outcomes when treated in facilities with high annual caseloads. Besides a decreased risk of in-hospital mortality, there is also a reduced risk of 1-year mortality in high-volume hospitals. In addition, there is evidence that adherence to already existing minimum caseload requirements reduces morbidity and mortality of pancreatic surgery in Germany. As a result of an insufficient centralization in the recent past, however, a large proportion of hospitals that perform pancreatic surgery still do not meet minimum caseload requirements.Specific measures (i.e. sanctions for failure to achieve minimum volumes) that initiate a sufficient centralization process without threatening patient access to surgical care are needed.
EVALuna2:15293